Use of Patient Preference Information in Benefit–Risk Assessment, Health Technology Assessment, and Pricing and Reimbursement Decisions: A Systematic Literature Review of Attempts and Initiatives - Chachoua, Lylia; Dabbous, Monique; François, Clément; Dussart, Claude; Aballéa, Samuel; Toumi, Mondher (Frontiers in Medicine, 2020)
Objectives: Inclusion of patient preference (PP) data in decision-making has been largely discussed in the recent years. Healthcare decision makers –regulatory and HTA- are more and more conscious of the need for a patient-centered approach to decide on optimal allocation of scarce money, time, and technological resources. This literature review aims to examine the use of and recommendations for the integration of PP in decision-making. Methods: A literature search was conducted through PubMed/Medline in May 2019 to identify publications on PP studies used to inform benefit-risk assessments (BRAs) and health technology assessments (HTAs) and patient-centered projects and guidelines related to the inclusion of PPs in health policy decision-making. After title and abstract screening and full texts review, selected publications were analyzed to retrieve data related to the collection, use, and/or submission of PPs informing BRA or HTA as well as attempts and initiatives in recommendations for PPs integration in decision-making processes. Results: Forty-nine articles were included: 24 attempts and pilot projects discussions and 25 PP elicitation studies. Quantitative approaches, particularly discrete choice experiments, were the most used (24 quantitative elicitation studies and 1 qualitative study). The objective of assessing PPs was to prioritize outcome-specific information, to value important treatment characteristics, to provide patient-focused benefit–risk trade-offs and appraise the patients’ willingness-to-pay for new technologies. Moreover, attempts and pilot projects to integrate PPs in BRAs and HTAs were identified at the European level and across countries but no clear recommendations have been issued yet. No less than 7 public and/or private initiatives have been undertaken by governmental agencies and independent organizations to set guidance targeting improvement of patients’ involvement in decision-making. Conclusion: Despite the initiatives undertaken, the pace of progress remains slow. The use of PPs remains poorly implemented and evidence of proper use of these data in decision-making is lacking. Guidelines and recommendations formalizing what is the purpose of collecting PPs, what methodology should be adopted, how, and who should be responsible for generating these data throughout the decision-making processes are needed to improve and empower integration of PPs in BRA and HTA.